Investigating teacher’s practices of TPR method in teaching vocabulary to young learners - Shabir, M. (ENGLISH JOURNAL, 2016)
This study seeks to investigate the practices of Total Physical Response (TPR) method by teacher in teaching English vocabulary to the fourth year students of elementary school. To achieve the objective, the writer observed intensively how a teacher at one of elementary schools in Cimahi put into practices the method for 4th grade students numbering 34 students; 18 girls and 16 boys. The writer found that the teacher’s practices of the TPR method had been successfully carried out as suggested by the method.